Pinealectomy affects bone mineral density and structure - an experimental study in sheep - Egermann, Marcus; Gerhardt, Christian; Barth, Alain; Maestroni, Georges J.; Schneider, Erich; Alini, Mauro (BMC musculoskeletal disorders, 2011)
Osteoporosis and associated fractures are a major public health burden and there is great need for a large animal model. Melatonin, the hormone of the pineal gland, has been shown to influence bone metabolism. This study aims to evaluate whether absence of melatonin due to pinealectomy affects the bone mass, structure and remodeling in an ovine animal model.